A Dual-Route Perspective of SARS-CoV-2 Infection: Lung- vs. Gut-specific Effects of ACE-2 Deficiency - Sajdel-Sulkowska, Elizabeth M. (Frontiers in Pharmacology, 2021)
SARS-CoV-2, primarily considered a respiratory virus, is increasingly recognized as having gastrointestinal aspects based on its presence in the gastrointestinal (GI) tract and feces. SARS-CoV-2 uses as its receptor angiotensin-converting enzyme 2 (ACE-2), a critical member of the renin-angiotensin-aldosterone system (RAAS) involved in the regulation of blood pressure and fluid system. In addition to the systemic endocrine functions, RAAS components are also involved in intracrine and organ-specific local functions. The angiotensin converting enzyme 2 (ACE-2) is a key component of RAAS and a receptor for SARS-CoV-2. It is expressed in many tissues with gastrointestinal (GI) tract ACE-2 levels far exceeding those in the respiratory tract. SARS-CoV-2 binding to its receptor results in a deficiency of ACE-2 activity in endocrine, intracrine and local lung and GI tract ACE-2. The local ACE-2 has different organ-specific functions including hypertension-independent activities; dysregulations of these functions may contribute to multiorgan COVID-19 pathology, its severity, long-term effects, and mortality. We review supporting evidence from this standpoint. Notably, COVID-19 comorbidities involving hypertension, obesity, heart disease, kidney disease, and diabetes are associated with gastrointestinal problems, and display ACE-2 deficits. While RAAS inhibitors, target both endocrine and intracrine ACE-2 activity, the deficit of the local ACE-2 activity in the lungs and more so in the gut have not been targeted. Consequently, the therapeutic approach to COVID-19 should be carefully reconsidered. Ongoing clinical trials testing oral probiotic bound ACE-2 delivery are promising.